Asymmetry in the functioning of Ukrainian and foreign banking systems in the conditions of globalization - Khmelyarchuk, Mariya; Kozlovskyi, Yurii (Ekonomika, 2015)
The article concentrates on the empirical substantiation of manifestations of asymmetry in the functioning of banking systems of different countries in the conditions of globalization, focusing attention on the functioning features of the banking system of Ukraine. According to the materials from the World Bank, asymmetric effects have been revealed in the functioning of national banking systems in terms of the indicators of their activities (capital ratio to assets, a share of nonperforming bank loans, interest rates on loans, and interest rate spread) as well as the percentage of the private sector bank crediting towards the GDP. The attention is focused on the fact that the effective functioning of the banking system of Ukraine is limited by high credit risks, ultra-high interest rates which, in addition to the political and economic instability in Ukraine, do not contribute to the post-crisis recovery of the national economy. The measures for overcoming the significant asymmetries in the functioning of the banking system of Ukraine in comparison with the banking systems of the developed countries have been offered.
Keywords: banks; national banking systems; globalization; asymmetries